The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/slct.202000579
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis and Biological Evaluation of 2‐(naphthoyl) iminothiazolidin‐4‐ones as Potential Anticancer Agents

Abstract: A library of novel naphthyl bearing 2-iminothiazolidin-4-ones (2-ITZDs) (2 a-2 q) was designed and synthesized through a facile route involving regioselective heterocyclization of unsymmetrical thioureas (1 a-1 q). The synthesis was achieved at ambient temperature in good to excellent yields under catalyst free conditions. The molecular structures of 2-ITZDs were elucidated by spectroscopic techniques such as FT-IR, 1 H-NMR and 13 C-NMR. X-ray structural data was used to establish the structure (2 o) unequivoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Recently, it has been reported that different thiazolidinone derivatives exerted CYP inhibition activity in several isoforms (CYP1A2, CYP3A4, and CYP2C19) at 10 μM, but there was no CYP inhibition activity of CYP2C9 and CYP2D6 in human and rat liver microsomes (Ashraf et al 2020 ). Unfortunately, the data on the CYP expression and/or activity after thiazolidinone treatment are limited.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that different thiazolidinone derivatives exerted CYP inhibition activity in several isoforms (CYP1A2, CYP3A4, and CYP2C19) at 10 μM, but there was no CYP inhibition activity of CYP2C9 and CYP2D6 in human and rat liver microsomes (Ashraf et al 2020 ). Unfortunately, the data on the CYP expression and/or activity after thiazolidinone treatment are limited.…”
Section: Discussionmentioning
confidence: 99%
“…Thiazolidinone motifs are biologically significant five-membered heterocycle that is very common substructures in various pharmacological active molecules and known to exhibit a wide range of biological activities such as anticancer, antifungal, anti-inflammatory, antimicrobial, antidiabetic, inhibiting neuraminidase of influenza virus, and anti-HIV, 29 antischistosomal activity. Among these are inhibitors for necroptosis, selective GSK-3β inhibitor, anticancer activity, 30 aldose reductase inhibitor, 31 potent antiproliferative agent and inhibitor for non-membrane protein tyrosine phosphate. The aforesaid facts inspired us to synthesize novel ethyl 3-adamantanyl-2-((2-methyl benzoyl)imino)-4-oxothiazolidin-5-ylidene acetates (5a–j) for the appraisal of elastase inhibition assay.…”
Section: Introductionmentioning
confidence: 99%
“…The MTT assay results revealed compound 169a as a promising derivative with IC 50 values of 19, 17, 7, 10, and 15 μM against A549, LNCap, MDA‐MB‐231, BxPC3, and MIAPaCa2, respectively. Further, the SAR study showed a better anticancer potential of the 2,6‐dichloro substituted derivative, compound 169a , as compared to trifluoromethyl, methoxy, and fluoro‐substituted thiazolidinone analogues [42].…”
Section: Synthetic Strategies and Biological Activity Profile Of 4‐th...mentioning
confidence: 99%